Pentecost and Sinai: The Festival of Weeks as a Celebration of the Sinai Event - Pak, Se-jin (The Library of Hebrew Bible / Old Testament Studies, 2009)
An examination of the evidence that the Festival of Weeks was the occasion for the celebration of the renewal of the covenant in the Second Temple period, encompassing chapters on the Hebrew Bible, book of Jubilees, Qumran Scrolls, and the New Testament (Luke-Acts and Ephesians)